Habitat preferences and spring temperature‐related abundance of German wasp Vespula germanica in its northern range. Issue 4 (22nd December 2017) - Sorvari, Jouni
Abstract: Global climate change causes range shifts in many insects. Urban areas and south‐facing slopes may provide a warmer environment for newcomers adapted to warmer climatic conditions. The German wasp ( Vespula germanica, Fabricius, 1793), which is native to central and southern Europe, has been expanding its range into Southern Finland since 2001. The association between the German wasp and its sister species, the common wasp ( V. vulgaris Linnaeus, 1758), with urban areas was studied in three cities in Finland. In addition, the numbers of German wasp catches during 7 years on south‐ and north‐facing riverbank slopes in SW‐Finland were compared and the association with spring temperature was analysed. The newcomer German wasp seemed to be associated with urban areas, while its sister species was associated with rural areas in two of the cities and urban areas in one of the three studied cities. In addition, the German wasp was more common in south‐facing than in north‐facing slopes of the river valley, while the direction of the slope was less important for the common wasp. Finally, the abundance of the German wasp but not the common wasp has increased with an increase in spring temperature. The preference of the German wasp for urban habitats and south‐facing slopes in Finland may be because those habitats are usually warmer than their surroundings and the species is well adapted for urban environments. These environments can act as stepping stones in species' range shifts driven by climate change.